Reproducibility of QM/MM Calculations for the SARS-CoV-2 Main Protease - Sun, Xiaoli; Ryde, Ulf ; 0000-0001-7653-8489 (Journal of Chemical Theory and Computation, 2025)
Combined quantum mechanics and molecular mechanics (QM/MM) calculations are a popular approach to study reaction mechanisms of enzymes. However, recently, the reproducibility of such calculations has been questioned, comparing the results of two software: NWChem and Q-Chem. Here, we continue and extend this study by including three additional software─ComQum, ORCA, and AMBER─using the same test case, the covalent attachment of the carmofur inhibitor to the catalytic Cys-145 residue of the SARS-CoV-2 main protease, using a quantum region of 83 atoms. We confirm that the various software programs give varying results for the reaction (ΔE) and activation (ΔE‡) energies. The main reason for the variation is how charges around the cleaved bonds between the QM and MM regions are treated, i.e., the charge-redistribution scheme. However, there are still differences of ∼10 kJ/mol between different implementations of the same method in ComQum and ORCA. Some of these problems can be solved by calculating the final energies with larger QM systems. We show that energies calculated with the big-QM approach are reasonably converged if atoms within 8 Å of the minimal QM region are included (∼1400 atoms), solvent-exposed charged residues are neutralized, and the calculation is performed in a continuum solvent with a dielectric constant of 80. On the other hand, we show that different setups of the protein lead to even larger differences in the calculated energies, by up to 114 kJ/mol. Even if the same approach is used and the only difference is how water molecules are added (by random) to the crystal structure, energies differ by 18-57 kJ/mol. The results also strongly depend on how much of the surrounding protein and solvent are relaxed in the calculations. Therefore, it seems that for a solvent-exposed active site, QM/MM calculations with minimized structures cannot be recommended. Instead, methods that incorporate dynamic effects and calculate free energies seem preferable.